Post-schizophrenic depression – problematic diagnosis - Stakhanov, K. (Journal of Education, Health and Sport, 2015)
The problem of depression in schizophrenia is one of the most urgent in modern psychiatry, but there is still no generally accepted approach to both the diagnosis of these conditions and to practical recommendations for optimizing therapeutic approaches. Therefore, this work of the author is devoted to the analysis of the scientific and theoretical substantiation of the problem of post-schizophrenic depression (PSD). The methods were analysis and synthesis of existing scientific-theoretical and experimental research in the field of PSD. The purpose of the study was to analyze the existing scientific achievements in the field of psychiatry, psychology and medicine to clarify all clinical and diagnostic aspects: the etiology of pathogenesis; clinics; definition and nosological qualification of the PSD. Since the volume and content of PSD as an independent diagnostic category, first identified in the ICD-10 (1994) in the section "Schizophrenia," does not allow comprehensive clarification of all clinical and diagnostic aspects, but only actualizes the issue of their: the etiology of pathogenesis; clinics; definition and nosological qualification. The solution of these issues is closely connected with the clarification of the clinical and psychopathological content of schizophrenia as a nosological unit and the improvement of its taxonomy; hence the study of the PSD is becoming increasingly relevant in the modern period.